The effect of fermented milk on the deciduous enamel in the presence and absence of fluoride: in vitro study - Pimentel Lopes De Oliveira, G. J. [UNESP]; Bomfim Da Silva, M. A.; Chaves De Souza, J. A. [UNESP]; Santos Alves Pereira, M.; Mendonça Cavalcante, A.; Limeira Dos Reis, J. I.; De Melo Santos, L. (My University, 2013)
Aim. This study assessed the effect of fermented milk on the enamel of primary teeth in the presence and absence of fluoride. Methods. Sixty enamel blocks (4×4 mm) underwent surface microhardness analysis (Knoop). The blocks were randomly distributed into 5 groups of 12 samples in each group according to the following treatments: Group 1) pH cycling and fermented milk (control); Group 2) pH cycling and dentifrice; Group 3) pH cycling and fermented milk and dentifrices; Group 4) varnish and pH cycling and fermented milk; Group 5) varnish and pH cycling and fermented milk and dentifrice. After the treatments, new microhardness determination was carried out and the surface microhardness change ratio was calculated (%SMH). The data were submitted to the Shapiro-Wilk normality test, ANOVA test, Tukey's test and paired t-test (P<0.05). Results. It was observed that after treatment, all groups showed statistically significant reduction (P<0.05) for initial surface microhardness. Group 1 showed the lowest microhardness (73.01+9.68 KNH) compared to groups 2, 3 and 4. Group 5 (172.5±45.85>KNH) showed a greater surface microhardness than Group 4 (122.0±22.33 KNH). Conclusion. It was concluded that the fermented milk adversely altered the microhardness of the samples and that fluorine contributes to a smaller reduction in the microhardness change ratio (SMH%). The combined solution of toothpaste with fluoride varnish provided a lower surface microhardness reduction of the samples.
Keywords: Cultured milk products; Dental enamel solubility; Fluor